2014
DOI: 10.1007/s10549-014-3208-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk after diagnosis by screening mammography of nonproliferative or proliferative benign breast disease: a study from a population-based screening program

Abstract: Benign breast disease increases the risk of breast cancer. This association has scarcely been evaluated in the context of breast cancer screening programs although it is a prevalent finding in mammography screening. We assessed the association of distinct categories of benign breast disease and subsequent risk of breast cancer, as well as the influence of a family history of breast cancer. A retrospective cohort study was conducted in 545,171 women aged 50–69 years biennially screened for breast cancer in Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 20 publications
8
41
1
6
Order By: Relevance
“…In keeping with findings from previous studies (5,17,25), there was no evidence from this study to support an association between obesity or family history and breast cancer risk among women with BBD overall. However, contrary to our finding of a null association between family history and breast cancer risk among women with proliferative BBD, several studies have provided evidence in support of elevated risk of breast cancer in relation to a positive family history of breast cancer (17,26,27). However, further studies are needed to confirm this.…”
Section: Discussioncontrasting
confidence: 99%
“…In keeping with findings from previous studies (5,17,25), there was no evidence from this study to support an association between obesity or family history and breast cancer risk among women with BBD overall. However, contrary to our finding of a null association between family history and breast cancer risk among women with proliferative BBD, several studies have provided evidence in support of elevated risk of breast cancer in relation to a positive family history of breast cancer (17,26,27). However, further studies are needed to confirm this.…”
Section: Discussioncontrasting
confidence: 99%
“…16 Benign breast hyperplasia/BBD without atypia is associated with a nearly two-fold increased breast cancer risk. 17-20 The presence of histopathologic indices of abnormal proliferation (such as atypia and lobular carcinoma in situ) within an otherwise benign breast biopsy confers higher risks for future breast cancer: four-to-five-fold relative risk for atypia and ten-fold for LCIS. 18-24 Several studies have furthermore confirmed that biopsy-proven BBD is a risk factor for future breast cancer in both AA and WA women.…”
Section: Discussionmentioning
confidence: 99%
“…In their seminal study, Dupont and Page found no increased breast cancer risk among women with nonproliferative BBD [12]. However, more recent research has found modest increased risk of breast cancer among nonproliferative lesions [9, 17, 41]. Wang et al in a companion study to the National Surgical Adjuvant Breast and Bowel Project (NSABP) Breast Cancer Prevention Trail found that women in the “lower category” of BBD had 1.6 times the risk of breast cancer compared to healthy women [41].…”
Section: Discussionmentioning
confidence: 99%
“…al. found nonproliferative lesions conferred a 2.23 fold (95% CI: 1.86–2.68) increased risk of breast cancer in a population based screening cohort [9]. Few studies have investigated risk factors for both proliferative and nonproliferative lesions given the mixed findings among nonproliferative lesions related to breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%